2012
DOI: 10.1152/ajpregu.00393.2012
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in activity and energy expenditure contribute to lean phenotype in Fischer 344 rats lacking the cholecystokinin-1 receptor gene

Abstract: CCK is hypothesized to inhibit meal size by acting at CCK1 receptors (CCK1R) on vagal afferent neurons that innervate the gastrointestinal tract and project to the hindbrain. Earlier studies have shown that obese Otsuka Long-Evans Tokushima Fatty (OLETF) rats, which carry a spontaneous null mutation of the CCK1R, are hyperphagic and obese. Recent findings show that rats with CCK1R-null gene on a Fischer 344 background (Cck1r(-/-)) are lean and normophagic. In this study, the metabolic phenotype of this rat str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Blood was collected for glucose measurements by tail vein nick and measured by the glucometer using the AlphaTRAK 2 blood glucose monitoring system (Abbott Laboratories, Abbott Park, IL) (11). Total cholesterol, triglycerides (TGs), and free fatty acids (FFAs) were measured using an enzymatic-based kit (Wako Chemicals, Richmond, VA).…”
Section: Glucose and Lipid Measurementsmentioning
confidence: 99%
“…Blood was collected for glucose measurements by tail vein nick and measured by the glucometer using the AlphaTRAK 2 blood glucose monitoring system (Abbott Laboratories, Abbott Park, IL) (11). Total cholesterol, triglycerides (TGs), and free fatty acids (FFAs) were measured using an enzymatic-based kit (Wako Chemicals, Richmond, VA).…”
Section: Glucose and Lipid Measurementsmentioning
confidence: 99%
“…We have found that this approach was suitable for measuring differences in NTS expression of OT receptor mRNA. In addition, we have used the Arcturus AutoPix Fluorescent LCM System to confirm the “expected” reduction in cholecystokinin-1 receptor (CCK1R) mRNA in both the ARH (–3.48 mm to –2.04 mm from Bregma; [334]) and dorsomedial hypothalamic nucleus (DMH) (–3.60 mm to –2.80 mm from Bregma; [334]) in rats that lack CCK1Rs relative to wild-type rats [36]. As before, slide-mounted cryostat sections (10 μm) of ARH and DMH were selected at 200 μm intervals, dehydrated in ethanol and xylene, and then air-dried (n=6 slides/brain).…”
Section: Laser-capture Microdissection Studies: Methodological Considmentioning
confidence: 99%
“…Slide-mounted cryostat sections (10 μm-thick) were generated through the ARH from ad libitum fed or 48-h fasted wild-type or cholecystokinin-1 receptor (CCK1R) knockout (KO) Fischer 344 rats ( left panel ) or ad libitum fed or 48-h fasted wild-type Sprague-Dawley rats ( right panel ). Sections were thawed briefly prior to dehydration in ethanol and xylene and allowed to air dry as described previously [29, 35, 36]. LCM was used to collect bilateral sections (10 μm-thick) from the ARH (200 μm intervals) from six anatomically matched levels and sections were mounted onto slides.…”
Section: Figmentioning
confidence: 99%
“…However, intraperitoneal (i.p.) injection of CCK-1 receptor antagonist stimulates food intake 10,[12][13][14][15][16][17][18][19] and thus i.p. injection of LGM will influence intrinsic CCK and leptin release due to the size of meal or energy intake.…”
Section: Signalling Interplay In Vivomentioning
confidence: 99%
“…The dominant receptor subtypes, CCK-1 and CCK-2 receptors, are both G q -coupled seven-transmembrane receptors 8 , 9 . CCK-1 receptors influence satiety, as CCK-1 agonists reduce food intake 10 , 11 whereas pharmacological blockage of CCK-1 receptors stimulate food intake 10 , 12 19 . CCK-1 receptors are localized in peripheral and central machinery known to control satiety, and their dense expression has been found in the pylorus, nodose ganglion, nucleus tractus solitarius, and hypothalamic satiety-controlling centres 20 .…”
Section: Introductionmentioning
confidence: 99%